KEPEMIMPINAN TRANSFORMASIONAL DALAM TINJAUAN SEJARAH DAN PERKEMBANGAN KAJIANNYA PADA BIDANG PENDIDIKAN - Binti Nasukah; Binti Maunah (STKIP Pesisir Selatan, 2021)
Transformational leadership is becoming the popular concepts in the management science for the last 30 years, as well as in the field of education management. To avoid an application in the education sector that is merely followed because of trending, it needs an understanding of the historical side of the transformational leadership model. Through the literature study, this study presented three things: (1) The history of the development of leadership theories; (2) The history of a transformational leadership theory model, and (3) the development of transformational leadership studies in the field of education. The development of leadership studies involving intrinsic and extrinsic motivational theories, has spawned the idea of an intrinsic transformational leadership, compared to extrinsic transactional leadership. Inspired by the writings of James McGregor Burns (1978), Bernard M. Bass (1990) created the concept of transformational leadership model, to popular and became an important study to be implemented in various sectors, including in the field of education. The study of transformational leadership in the area of pedagogy has come to the conclusion that transformational leadership is an ideal representation of the practice at school in the 21st century.